SCIENTIFIC RESEARCH ACTIVITY IS THE MAIN DRIVING FORCE OF SOCIETY’S DEVELOPMENT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article provides a scientific and theoretical analysis of the role and importance of research activity in societal development. The impact of scientific research on the advancement of science and technology, socio-economic development, and innovation processes is examined. Particular attention is paid to the integration of education and research activities. The article also highlights the significance of research in the context of digital transformation and proposes practical recommendations for the development of research activities in Uzbekistan.